Beer, hyponatraemia and cardiac conduction defects. (14th March 2018) - Mifsud, Simon; Schembri, Emma Louise; Mercieca Balbi, Matthew; Gruppetta, Mark; Clark, James
Abstract : The authors report a case of a 68-year-old man who was diagnosed with an irreversible second-degree atrioventricular (AV) Mobitz II 2:1 block temporally associated with profound hyponatraemia. The cause of the hyponatraemia was beer potomania. The co-occurrence of reversible first, second and third-degree heart blocks and hyponatraemia has been described in a few published case reports. However, this case is noteworthy as the AV block persisted, despite correction of serum sodium concentration as opposed to other published cases, which meant that the patient required a permanent pacemaker.